2012
DOI: 10.1007/s00262-012-1307-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy broadens the range of tumor antigens seen by cytotoxic CD8+ T cells in vivo

Abstract: Cytotoxic chemotherapies may expose the immune system to high levels of tumor antigens and expand the CD8(+) T-cell response to include weak or subdominant antigens. Here, we evaluated the in vivo CTL response to tumor antigens using a murine mesothelioma tumor cell line transfected with a neotumor antigen, ovalbumin, that contains a known hierarchy of epitopes for MHC class I molecules. We show that as tumors progress, effector CTLs are generated in vivo that focus on the dominant epitope SIINFEKL, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 40 publications
1
73
0
2
Order By: Relevance
“…Interestingly, CDDP’s ability to upregulate MHC class I expression may not be limited to just tumor cells but, as Jackaman et al illustrated, CDDP may also increase MHC class I expression on antigen presenting cells (APCs) (14). In a murine mesothelioma model, the authors treated tumor-bearing mice with either two doses of CDDP or a PBS control and demonstrated that tumor-associated CD11c + dendritic cells from mice treated with CDDP had greater MHC class I expression than did the dendritic cells from control mice (14).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Interestingly, CDDP’s ability to upregulate MHC class I expression may not be limited to just tumor cells but, as Jackaman et al illustrated, CDDP may also increase MHC class I expression on antigen presenting cells (APCs) (14). In a murine mesothelioma model, the authors treated tumor-bearing mice with either two doses of CDDP or a PBS control and demonstrated that tumor-associated CD11c + dendritic cells from mice treated with CDDP had greater MHC class I expression than did the dendritic cells from control mice (14).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…This may be via expression of HMG proteins that bind platinum complexes to cause repair shielding and initiate apoptosis. 23 We have shown that while cisplatin only slightly enhances in vivo presentation of dominant tumor antigens to T cells in draining lymph nodes, both cisplatin and gemcitabine expand the CTL response to weaker subdominant tumor epitopes 24 ; a feature that may be key to tumor destruction as immune tolerance mechanisms are likely to delete responses to dominant epitopes. Moreover, immune-relevant metagene analyses have shown a significant positive correlation with response rates for BC to chemotherapy, in particular to a CXCL13-centered metagene signature reflecting the intratumoral presence of activated IFNg-producing T cells.…”
Section: Chemotherapy and The Anticancer Immune Responsementioning
confidence: 99%
“…Ce changement de répertoire pourrait résulter de différences d'activation des lymphocytes T, d'affinité des TCR (T cell receptor), d'expression de molécules inhibitrices, etc. Jackaman et al ont par ailleurs montré que la chimiothérapie peut révéler des antigènes tumoraux sous-dominants contre lesquels une réponse n'est induite qu'après un traitement [11]. L'ensemble de ces observations suggèrent une action directe (indépendante de la présentation des antigènes tumoraux) du traitement chimiothérapeutique sur l'activation des lymphocytes T. Chez des patients atteints de mélanome, ces chimiokines sont également augmentées dans les lésions qui sont sensibles à la chimiothérapie [12].…”
Section: Les Débuts De La Chimiothérapieunclassified